Avaliação da capacidade de infiltração de solos submetidos a diferentes tipos de manejo - Mendonça, Luiz Alberto Ribeiro; Vásquez, Manuel Antonio Navarro; Feitosa, José Valmir [UNESP]; Oliveira, Juliana Filgueiras de; Franca, Raimunda Moreira da; Vásquez, Edilza Maria Felipe; Frischkorn, Horst (My University, 2009)
Inadequate vegetation and soil management leads to physical changes that affect aquifer recharge. The Araripe Plateau feeds an elevated number of springs on its northern slope; however, there are indications that their yield is decreasing. Through this research, it was studied the infiltration capacity of soils under different types of management. Soil samples from 21 sites were grouped into four groups. Group 1 represents areas of preserved vegetation, the others, anthropized ones. It was observed that soil moisture and infiltration capacity are linearly well correlated with organic matter; mean soil moisture during the dry season was significantly higher for Group 1 than for the other groups, even during the rainy season and anthropized areas show low organic matter contents, soil moisture, and infiltration capacity, indicating modifications in the soil's structure that reduce aquifer recharge.
Evaluation of the infiltration capacity of soils under different types of management
Keywords: Araripe plateau; Infiltration capacity; Organic matter; Recharge